STUDENT TRAINING CENTER DI KOTA PEKANBARU DENGAN PENERAPAN PENDEKATAN NEURO-ARCHITECTURE - prananda, adelia (Jurnal Mahasiswa Departemen Arsitektur, 2025)
ABSTRACT   Pekanbaru City faces challanges in providing non-academic educational facilities, particularly in sports and cultural arts. This gap affects the holistic development of stuudents. To address this, the Student Training Center is designed as a training facility for students from elementary to higher education levels. The center accommodates training in sports (football, long jump, gymnastics, chess, pencak silat, karate) and cultural arts (guitar, debate, newscasting, monologue, storytelling, pantomime, speech, and innovation. The building design adopt a thematic neuro-architecture approach, integrating elements such as color, curved forms with repeating patterns, natural components, design balance, and active circulation. This aims to create a physical environment that stimulates students’ cognitive, emotional, and social engagement. A pragmatic methodological approach is applied, using trial and erro strategies in mass exploration to develop an architecturally contextual design. This approach emhasizes rational decisios and their real impact on building function and spatial experience. With this startegic and responsive design, the Student Training center is expected to become a purposeful facility that supports structured and continuous development of student’ non-academic achievements in Pekanbaru City.   Keywords: Training Center, Neuro-Architecture, Sports, Cultural Arts